2021
DOI: 10.1016/j.waojou.2021.100550
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review of infant feeding food allergy prevention guidelines – can we AGREE?

Abstract: Food allergy is a significant issue worldwide, particularly in Westernised countries. There is no clear explanation why food allergy appears to have increased so rapidly in recent years, particularly in young children, hence ongoing research to identify effective primary prevention strategies. Food allergy prevention guidelines for health professionals have been developed based on existing clinical trial evidence for effective translation and implementation. As these guidelines underpin clinical practice, it i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
31
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(34 citation statements)
references
References 64 publications
(424 reference statements)
1
31
0
2
Order By: Relevance
“…The use of soy-based infant formulas in the prevention of atopic diseases in high-risk infants seems controversial [ 339 , 347 ], with studies showing some prophylactic effect of soy-based infant formulas when compared to cow’s milk-based formulas [ 353 , 354 ], whereas other studies did not show such effect [ 355 , 356 ]. Yet, in a meta-analysis, Osborn and Sinn concluded that soy-based infant formulas cannot be recommended for use in the prevention of food allergies in high-risk infants [ 357 ], which is generally supported by most guidelines [ 358 ]. For example, EAACI recommends against using soy-based formula in the first 6 months of life as a means of preventing food allergy [ 81 ].…”
Section: Plant-based Infant Formulasmentioning
confidence: 99%
“…The use of soy-based infant formulas in the prevention of atopic diseases in high-risk infants seems controversial [ 339 , 347 ], with studies showing some prophylactic effect of soy-based infant formulas when compared to cow’s milk-based formulas [ 353 , 354 ], whereas other studies did not show such effect [ 355 , 356 ]. Yet, in a meta-analysis, Osborn and Sinn concluded that soy-based infant formulas cannot be recommended for use in the prevention of food allergies in high-risk infants [ 357 ], which is generally supported by most guidelines [ 358 ]. For example, EAACI recommends against using soy-based formula in the first 6 months of life as a means of preventing food allergy [ 81 ].…”
Section: Plant-based Infant Formulasmentioning
confidence: 99%
“…In some non-IgE-mediated allergies, such as pseudo-allergies, mast cell activation also plays an important role in the onset of allergic symptoms [3][4][5]. In developed countries, the prevalence of food allergies is 6% to 10% in infants and 2% to 5% in adults [6][7][8][9], indicating that they are more common in children. However, it has recently been demonstrated that some patients with irritable bowel syndrome (IBS) have abdominal pain caused by local IgE-mediated food allergy reactions [10].…”
Section: Introductionmentioning
confidence: 99%
“…One of the key questions in relation to food allergy is when potentially allergenic foods should be introduced into the diet of infants to induce tolerance. As a result of several intervention trials on early introduction of food allergens, such as peanut and egg, there is increasing scientific consensus that earlier introduction of these foods can be recommended [11].…”
Section: Introductionmentioning
confidence: 99%
“…As a result of all these new insights, guidelines have been updated in many different countries. These guidelines have been reviewed in a systematic review by Vale et al [11]. These changes are also illustrated in the policy document of the American Academy of Pediatrics [35,36] that shifted from the statement that "there are insufficient data to document a protective effect of any dietary intervention beyond 4 to 6 months of age for the development of atopic disease" in 2008 [35] to "There is no evidence that delaying the introduction of allergenic foods, including peanuts, eggs, and fish, beyond 4 to 6 months prevents atopic disease.…”
Section: Early Introduction Of Food Allergensmentioning
confidence: 99%